2021
DOI: 10.1097/ypg.0000000000000287
|View full text |Cite
|
Sign up to set email alerts
|

CYP2C19 polymorphisms are associated with severity of depression at initial evaluation and after the treatment independently of the prescribed medications: 4 weeks prospective study

Abstract: Danute Balkeliene d,e Algirdas Utkus d,e and Edgaras Dlugauskas a,e Background The cytochrome P-450 2C19 (CYP2C19) enzyme is involved in the metabolism of numerous antidepressants. It also metabolises some endogenous substrates, which could also confer to vulnerability. We aimed to establish whether the severity of depression and treatment response are associated with the genetically predicted CYP2C19 phenotype. MethodsWe assessed the CYP2C19 genotypepredicted metabolic phenotypes (normal, intermediate or ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…Recent studies have suggested that impaired CYP2C19 metabolizers had higher self-rated Beck Depression Inventory-II scores than normal metabolizers. Damaged CYP2C19 enzyme activity was associated with more severe MDD, despite CYP2C19-metabolized medication treatment and treatment discrepancy status [ 7 ]. CYP2C19 polymorphism has been demonstrated to affect the conversion and degradation of endogenous compounds, including psychoactive steroid hormones (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested that impaired CYP2C19 metabolizers had higher self-rated Beck Depression Inventory-II scores than normal metabolizers. Damaged CYP2C19 enzyme activity was associated with more severe MDD, despite CYP2C19-metabolized medication treatment and treatment discrepancy status [ 7 ]. CYP2C19 polymorphism has been demonstrated to affect the conversion and degradation of endogenous compounds, including psychoactive steroid hormones (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies on risk variants contributing to psychiatry disorders, 13 genes containing 20 SNPs were selected for further analysis. CYP2C19 (rs12248560, rs4986893, rs4244285) was obtained from the findings of a 4-week prospective study by Strumila et al [ 7 ]. CYP2C9 (rs1057910) was chosen from a case-control study in a European population [ 14 16 ].…”
Section: Methodsmentioning
confidence: 99%